Speciation of nanoscale objects by nanoparticle imprinted matrices. Issue 29 (9th March 2016) - Hitrik, Maria; Pisman, Yamit; Wittstock, Gunther; Mandler, Daniel
Abstract : Self-assembly of polymer-template nanoparticle composites followed electrooxidation of the nanoparticles yielded nanoparticle imprinted matrices that recognized selectively nanoparticles with the same size and the same ligand shell as the template nanoparticles. Abstract : The toxicity of nanoparticles is not only a function of the constituting material but depends largely on their size, shape and stabilizing shell. Hence, the speciation of nanoscale objects, namely, their detection and separation based on the different species, similarly to heavy metals, is of outmost importance. Here we demonstrate the speciation of gold nanoparticles (AuNPs) and their electrochemical detection using the concept of "nanoparticles imprinted matrices" (NAIM). Negatively charged AuNPs are adsorbed as templates on a conducting surface previously modified with polyethylenimine (PEI). The selective matrix is formed by the adsorption of either oleic acid (OA) or poly(acrylic acid) (PAA) on the non-occupied areas. The AuNPs are removed by electrooxidation to form complementary voids. These voids are able to recognize the AuNPs selectively based on their size. Furthermore, the selectivity could be improved by adsorbing an additional layer of 1-hexadecylamine, which deepened the voids. Interestingly, silver nanoparticles (AgNPs) were also recognized if their size matched those of the template AuNPs. The steps in assembling the NAIMs and the reuptake of the nanoparticles were characterized carefully. The prospects for the analytical use of NAIMs, which are simple, of small dimension, cost-efficient and portable, are in the sensing and separation of nanoobjects.